Fertilizer Recommendation Philosophies - George Hochmuth; Rao Mylavarapu; Ed Hanlon (EDIS)
Farmers receive varying fertilizer recommendations depending on which lab they consult because labs employ different chemical methods and procedures to analyze the samples and subscribe to different fertilizer recommendation philosophies. This 4-page fact sheet explains the main soil-test philosophies, their basis, and their applications, and explains why the Sufficiency Level of Available Nutrient philosophy (SLAN), also called the Crop Nutrient Requirement (CNR), is most likely to be the best to govern fertilizer recommendations in Florida today. Written by George Hochmuth, Rao Mylavarapu, and Ed Hanlon, and published by the UF Department of Soil and Water Science, October 2014. (Photo by George Hochmuth, UF/IFAS)